The Selection of Reliable Reference Genes for RT-qPCR Analysis of Anisakis simplex Sensu Stricto Gene Expression from Different Developmental Stages - Łopieńska-Biernat, Elżbieta (Acta Parasitol, 2020)
BACKGROUND: Anisakis simplex s. s. is a parasitic nematode with a complex life cycle in which humans can become accidental hosts by consuming raw or not fully cooked fish containing L3 larvae. The growing popularity of raw fish dishes has contributed to an increase in the incidence of anisakiasis, which has spurred scientific efforts to develop new methods for diagnosing and treating the disease and also to investigate the gene expression at different developmental stages of this parasite. The identification of reference genes suitable for the normalization of RT-qPCR data has not been studied with respect to A. simplex s. s. METHODS: In the present study, eight candidate reference genes were analyzed in A. simplex s. s. at two different developmental stages: L3 and L4. The expression stability of these genes was assessed by geNorm and NormFinder softwares. RESULTS: In general, our results identified translation elongation factor 1α (ef-1α) and peptidyl-prolyl isomerase 12 (ppi12) as the most stable genes in L3 and L4 developmental stages of A. simplex s. s. Validation of the selected reference genes was performed by profiling the expression of the nuclear hormone receptor gene (nhr 48) in different developmental stages. CONCLUSIONS: This first analysis selecting suitable reference genes for RT-qPCR in A. simplex s. s. will facilitate future functional analyses and deep mining of genetic resources in this parasitic nematode. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.2478/s11686-020-00220-3) contains supplementary material, which is available to authorized users.